Schizaraeus fouquei sp. nov., the first record of schizaraeus from Peru (Coleoptera: Tenebrionidae: Stenosini) - Giraldo-Mendoza A.E. (2020)
A new species of Stenosini (Coleoptera: Tenebrionidae: Pimeliinae), Schizaraeus fouquei sp. nov. is described from southern Andes of Peru: Apurímac and Cusco regions. Prior to this study, Schizaraeus Kulzer, 1955 was monotypic with one species, S. acuticosta Kulzer, 1955 from Catamarca Province in Argentina. We present habitus photographs of both species, scanning electron micrographs of external morphology of the new species, a distribution map, and a comparison of the characters of both species of the genus. © 2020 The Authors.